A scoping review of Advanced Practice Registered Nurses Consensus Model outcomes: Part four of a four-part series on critical topics identified by the 2015 Nurse Practitioner Research Agenda. Issue 12 (December 2018) - Litchman, Michelle L.; Schlepko, Thomas; Rowley, Tom; McFarland, Mary; Fiander, Michelle
ABSTRACT: Background and purpose: The Advanced Practice Registered Nurses (APRN) Consensus Model was produced by the APRN Joint Dialogue Group in 2008. The aim of the Consensus Model is to guide state boards on the implementation of APRN practice components, including licensure, accreditation, certification, and education and to clarify the legal scope of practice and APRN roles. The purpose of this scoping review and gap analysis was to appraise the evidence related to patient, nurse practitioner (NP) and organizational outcomes resulting from the Consensus Model. Methods: A scoping review of research studies and grey literature reports was conducted and focused on the outcomes and key concepts related to the Consensus Model. Areas of foci included patients, NPs, and organizations. A subsequent gap analysis was conducted. Conclusions: Several positive findings related to the Consensus Model, or components thereof, were identified for patient, NP, and organizational outcomes on various levels. Research gaps exist. Additional research is needed to fully evaluate the health outcomes on a broader scale. Implications for practice: Existing evidence may support NPs and supporting organizations to further legislative efforts to more fully implement the Consensus Model nationwide. Abstract : Supplemental Digital Content is Available in the Text.